2016
DOI: 10.1016/j.applanim.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of novel food by horses: The influence of food cues and nutrient composition

Abstract: Compared to ruminants little is known about how horses modulate food intake and learn about flavour-to-post-ingestive consequences. While it has been suggested that due to hindgut fermentation horse's foraging preferences may be largely influenced by sensory input (e.g. volatiles), it has been established that horses are able to differentiate and select familiar foods (e.g. concentrates and hay) based on nutritional content. Yet it remains unclear how this translates to the acceptance of nutritious novel foods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…According with van den Berg and Hinch (2016), an adaptation of 3-4 days seemed to be necessary to reduce the variability following the introduction of a new odour in horses. These results were in accordance with another study of the same researchers (van den Berg et al, 2016c). Similar conclusion were found by Hinch et al (Hinch et al, 2004) showing that the association of a novel feed (wheat) with a familiar odour or flavour (alfalfa) seemed to decrease the variability in intake and to increase the total intake of the novel feed compared to the control group.…”
Section: Palatability Testssupporting
confidence: 92%
“…According with van den Berg and Hinch (2016), an adaptation of 3-4 days seemed to be necessary to reduce the variability following the introduction of a new odour in horses. These results were in accordance with another study of the same researchers (van den Berg et al, 2016c). Similar conclusion were found by Hinch et al (Hinch et al, 2004) showing that the association of a novel feed (wheat) with a familiar odour or flavour (alfalfa) seemed to decrease the variability in intake and to increase the total intake of the novel feed compared to the control group.…”
Section: Palatability Testssupporting
confidence: 92%
“…This difference was less evident when a sweetener was added to the diet, an observation supported by the mean intake measures showing a ranking based on protein content but there were no significant differences in intake for the LP+ and HP diets. A similar ranking was also recorded in the multiple-choice test and these findings are in accord with other studies that have reported that preferences and intake are linked to macronutrient content (Laut et al, 1985;Cairns et al, 2002;Goodwin et al, 2005a;Redgate et al, 2014;van den Berg et al, 2016b). Such studies demonstrate that horses can discriminate between diets based on both energy and CP content, even if foods are novel and regardless of flavour (odour) preferences.…”
Section: The Influence Of Nutrients On Diet Selectionsupporting
confidence: 80%
“…Sweet odour (banana, coconut) increased the forage intake in comparison with the same feedstuff without sweet odour (Van den Berg, Giagos, Lee, Brown, Cawdell‐Smith, et al, 2016). In another study, a familiar odour (fresh lucerne) has been shown to have a positive effect on the intake of a novel food in horses (Van den Berg, Giagos, Lee, Brown, & Hinch, 2016). Whether MS has such a sweet or familiar odour is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the presence of secondary metabolites, such as bitter substances, may influence the taste of forages but also various studies have shown that horses prefer feeds rich in carbohydrates, such as sugars (Redgate et al, 2014), or high in protein (Rodiek & Jones, 2012; Van den Berg, Giagos, Lee, Brown, Cawdell‐Smith, et al, 2016; van den Berg et al, 2016; van den Berg et al, 2016). In the present study, MS had higher content of CP, NFE, such as sugars or starch, and CFAT compared to hay, which may relate to a high palatability of MS.…”
Section: Discussionmentioning
confidence: 99%